F(x) = x/2
g(x) = x - 3
f(8) = 8/2 = 4
g(f(x)) = 4 - 3 = 1
Answer g(f(8)) = 1
Answer:
x = 3
Step-by-step explanation:
We need it in factorized form to get x.
If the quadratic equation can be divided by a-2 the first part is:
(a-2)
Now to get a², the a must be multpilied by itself. So
(a-2)(a)
To get -10, -2 must be multiplied by 5. So:
(a-2)(a+5)
we can expand to get x
a² + 5a - 2a -10
a² + 3a - 10
a² + ax - 10
x = 3
Answer:
(x - 9)(x - 3)
Step-by-step explanation:
Step 1: Write out quadratic
x² - 12x + 27
Step 2: Factor
<em>What 2 numbers add up to -12 and multiply to 27?</em>
-9 and -3 add up to -12 and multiply to 27.
(x - 9)(x - 3)
Answer:
4
Step-by-step explanation:btw can i have brainliest?
The answer to this question is:
9x+8/3x^2